Amperometric Measurements and Dynamic Models Reveal a Mechanism for How Zinc Alters Neurotransmitter Release. Issue 8 (6th February 2020) - Ren, Lin; Oleinick, Alexander; Svir, Irina; Amatore, Christian; Ewing, Andrew G.
Abstract: Zinc, a suspected potentiator of learning and memory, is shown to affect exocytotic release and storage in neurotransmitter‐containing vesicles. Structural and size analysis of the vesicular dense core and halo using transmission electron microscopy was combined with single‐cell amperometry to study the vesicle size changes induced after zinc treatment and to compare these changes to theoretical predictions based on the concept of partial release as opposed to full quantal release. This powerful combined analytical approach establishes the existence of an unsuspected strong link between vesicle structure and exocytotic dynamics, which can be used to explain the mechanism of regulation of synaptic plasticity by Zn 2+ through modulation of neurotransmitter release. Abstract : From dense core to halo : Structural and size analysis of the vesicular dense core and halo using TEM was combined with monitoring and modelling single‐cell amperometric responses to study the vesicle size changes induced after zinc treatment and to explain the regulation mechanism of synaptic plasticity by Zn 2+ through modulation of neurotransmitter release.